ASPEK-ASPEK KECERDASAN SPIRITUAL DALAM KONSEP PENDIDIKAN LUQMAN HAKIM - Ahmad Fauzi (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2019)
The Children are jewel the heart and pedestal of the parents, so every parent will surely give the best for their children. Nowadays there are many children not good in attitude and personality. This is very worrying, because they are hope of the nation. Many parents prefer education for leads to increase Intelligence Quotient (IQ), while those related to Spiritual Quotient (SQ), the religious quality side is less attention. To limit discussion, this article will explore the aspects of developing spiritual intelligence in Luqman education. Islamic education is the best foundation to everyone for survival in the future. The concept of Luqman education is spiritual education, such as tauhid (prohibited shirk) the purification of the soul from the arrogant, arrogant nature. Social education, such as amar ma’ruf nahi munkar, not arrogant .The aspects of developing spiritual intelligence in Luqman’s letter verses 13-17 are Monotheism, personal resilience and social toughness.